Decreasing Rice Supply as the Impact Of The Government’s Policy on Rice Grain Purchasing Price - RETNO LANTARSIH; DWIDJONO HADI DARWANTO; JANGKUNG HANDOYO MULYO (Jurnal Studi Pemerintahan, 2015)
This research aimed at examining: (1) rice supply adjustment for the long-term equilibrium (2) the impact of the government’s policies on rice grain purchasing price to the rice supply, (3) and factors influencing the long-term and short-term rice supply in the rice-producing regions in Indonesia. This research used the panel data regression with the error correction model approach. The data were the yearly time series data of 1987 through 2008. The resultsshowed that (1) the rice supply adjustment for the long-term equilibrium was at 68%, (2) in the long term, the government’s policies on rice grain purchasing price reduced the rice supply, (3) in the long term, the rice retail price, the rain fall, and the technology had a positive influence on the rice supply, while the cassava and soybean prices had a negative influence. In the short term, the rice retail price and technology had a positive influence, while thecassava and soybean prices and the monetary crisis dummy had a negative influence to the rice supply in the rice-producing regions in Indonesia. KEY WORDS: rice supply, error correction model, panel data, Indonesia